2017
DOI: 10.1136/annrheumdis-2016-210823
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib inhibits macrophage activation and ameliorates vascular and fibrotic manifestations in the Fra2 mouse model of systemic sclerosis

Abstract: Nintedanib targets core features of SSc in Fra2-transgenic mice and ameliorates histological features of pulmonary arterial hypertension, destructive microangiopathy and pulmonary and dermal fibrosis. These data might have direct implications for the ongoing phase III clinical trial with nintedanib in SSc-associated interstitial lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
123
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(145 citation statements)
references
References 39 publications
8
123
2
5
Order By: Relevance
“…Thus, the possibility remain that differences in the administration route of nintedanib may be the cause of the contradictory results. In contrast, Huang et al reported that chronic treatment with nintedanib reduced pulmonary vascular remodeling in the Fos-related antigen-2 mouse model of systemic sclerosis (46), which was supportive of our results. On the other hand, another more recent study showed that chronic treatment with nintedanib of established late-phase PAH, from 8 to 11 weeks, did not improved pulmonary hemodynamics and vascular remodeling in SuHx rats (43).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the possibility remain that differences in the administration route of nintedanib may be the cause of the contradictory results. In contrast, Huang et al reported that chronic treatment with nintedanib reduced pulmonary vascular remodeling in the Fos-related antigen-2 mouse model of systemic sclerosis (46), which was supportive of our results. On the other hand, another more recent study showed that chronic treatment with nintedanib of established late-phase PAH, from 8 to 11 weeks, did not improved pulmonary hemodynamics and vascular remodeling in SuHx rats (43).…”
Section: Discussionsupporting
confidence: 91%
“…Recently nintedanib, an inhibitor of the receptor tyrosine kinase platelet‐derived growth factor receptor, fibroblast growth factor receptor and vascular endothelial growth factor receptor, blocked myofibroblast differentiation and subsequent fibrosis in a mouse model of SSc. Interestingly, these nintedanib‐mediated anti‐fibrotic effects were associated with reduced numbers of M2 macrophages .…”
Section: Macrophagesmentioning
confidence: 99%
“…Consistently, several lines of evidence have shown that celecoxib was able to promote M2‐M1 macrophage conversion or M2 phenotype recruitment suppression in mouse models of cancer or wound healing, thus providing a clue whereby this agent may be capable of reducing reactive stroma features. Similarly, nintedanib has also demonstrated ability to impair M2 macrophage activation in fibrotic milieu . This drug has also inhibited TGF‐β‐induced fibroblast‐to‐myofibroblast differentiation in studies of idiopathic pulmonary fibrosis, whose microenvironment is reminiscent of cancer‐associated reactive stroma …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, nintedanib has also demonstrated ability to impair M2 macrophage activation in fibrotic milieu. 81 This drug has also inhibited TGF-β-induced fibroblast-to-myofibroblast differentiation in studies of idiopathic pulmonary fibrosis, whose microenvironment is reminiscent of cancer-associated reactive stroma. 62 TGF-β is known as the main inducer of CAF/myofibroblast differentiation during reactive stroma development.…”
Section: Discussionmentioning
confidence: 99%